2016
DOI: 10.1186/s40658-016-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure of the spleen during 177Lu-DOTATATE treatment and its correlation with haematological toxicity and spleen volume

Abstract: BackgroundSomatostatin analogue-based radionuclide therapy with 177Lu-DOTATATE is an important treatment option for patients with advanced neuroendocrine tumours overexpressing somatostatin receptors. In addition to the kidneys, the bone marrow is a major dose-limiting organ. The correlation between developed haematological toxicity and absorbed dose to the bone marrow is poor, which indicates that other factors affect haematological response. The spleen has an important role in the haematopoetic system, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 31 publications
3
22
1
3
Order By: Relevance
“…Hematological toxicity according to hemoglobin counts was moderately but significantly correlated with total absorbed spleen dose which supported the possibility that radiation exposure of the spleen affects overall hematological response during Lu-177 DOTATATE treatment [33]. On the other hand, a previous study has reported that hematological toxicity after peptide receptor radionuclide therapy is not related to the radiation dose to the spleen [34].…”
Section: Splenic Uptake On Sstr Imaging Studiessupporting
confidence: 50%
“…Hematological toxicity according to hemoglobin counts was moderately but significantly correlated with total absorbed spleen dose which supported the possibility that radiation exposure of the spleen affects overall hematological response during Lu-177 DOTATATE treatment [33]. On the other hand, a previous study has reported that hematological toxicity after peptide receptor radionuclide therapy is not related to the radiation dose to the spleen [34].…”
Section: Splenic Uptake On Sstr Imaging Studiessupporting
confidence: 50%
“…Several articles already reported on patient dosimetry of 177 Lu-DOTATATE. 1,5,8,11,[63][64][65][66][67][69][70][71][72] Our objective was to assess the performance of existing commercial solutions for dosimetry purposes, which is why we selected a reduced number of clinical cases and organs, and did not considered tumors or image-based bone marrow dosimetry.…”
Section: C Clinical Datamentioning
confidence: 99%
“…9). Given the very low uptake of 177 Lu in the mouse spleen (0.43±0.23%ID/g at 72 h), radiation exposure seems an unlikely source in mouse, although in humans the spleen receives a non-negligible dose following 177 Lu-DOTATATE (4.5-15 Gy over 2-5 cycles) (27). Notably, in our experimental setup, we observed no differences in the uptake of 111 Inanti-γH2AX-TAT in the kidneys of the mice, the tissue that is exposed most to 177 Lu radiation dose, second only to the tumor.…”
Section: Dotatate and 111mentioning
confidence: 99%